Israel and NATO: Which course will relations take? - Thomas Papenroth (Stiftung Wissenschaft und Politik (SWP), 2005)
The debate over a new strategic alignment for Israel has received further momentum since the first visit of a NATO Secretary General to Israel in February, 2005. Israel must ask itself if a stronger presence in the Euro-Atlantic community would better serve its security than the political unilateralism which it largely exercises at present. Israel has always been loathe to take on coalition commitments, as political autonomy is one of the guiding principles of its actions. Since the Six-Day War (1967), a special partnership has developed with the USA, which annually provides Israel with, among other things, up to three billion US dollars in economic and military support.A stronger presence in the Euro-Atlantic community does not mean full NATO mem-bership for Israel. This remains unrealistic in the long term, but a process of mutual rapprochement can be initiated. In principle there are three options: first, the further development of relations in the framework of the Mediterranean Dialogue, second, Israel's admission to the Partnership for Peace program (PFP) and third, the deepening of bilateral contacts. (SWP-Comments / SWP)
Keywords: 320